Framing an International Summer School Project in Transylvania into Three Dimensions of the Hofstede’s Model - Florin Nechita; Hiromasa Tanaka (Kulttuurikirjon sadonkorjuu / Intercultural Harvest, 2021)
The paper examines whether the six dimensions are effective to describe the participants’ behaviour in an intercultural project-based program. Use of Hofstede's model dimensions are believed to provide “objective” description of national cultures and help people in raising awareness of their styles and stance to deal with different culture(s). The development of the paper is based on the results of a project initiated by two universities, Transilvania University of Brasov and Meisei University Tokyo, which aimed to cover some objectives in order to provide a framework for an extracurricular project-based learning for their students.
Keywords: Hofstede model; intangible heritage; summer school; project-based learning